Islamic Communication Pattern of Judges in Dealing Conflict of Muslim Families in the Religious Court Medan - Maria Ulfa Batubara; Lahmuddin Lubis; Syukur Kholil (Budapest International Research and Critics University, 2019)
This study deals with Islamic Communication Pattern of Judges in Dealing Conflict of Muslim Families in the Religious Court Medan. The research methods used in this study is qualitative research. The results shows that the most important thing from the judge's communication pattern, namely the pattern of two-way communication or feedback (Two way traffic communication), namely Communicators and Communities to exchange functions in carrying out their functions, Communicators in the first stage became communicants and at the next stage alternating function. The pattern of Islamic communication as a strategy carried out by the judge is the selection of words or language that is good and a subtle tone of voice between the judge as a mediator and a married couple, so that they can feel comfortable when in the mediation process. The mediator is patient so that the husband and wife feel comfortable and easier to communicate. By providing Islamic communication to advice couples in different characters, various problems and other family interventions can provide the best solution for couples who are in the process of divorce, the judge also tries to make the husband and wife change their mind to want to revoke the divorce lawsuit and refer back.